1989
DOI: 10.1128/aac.33.9.1544
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic evaluation of free and liposome-encapsulated amphotericin B in the treatment of systemic candidiasis in mice

Abstract: Various doses of amphotericin B encapsulated into unilamellar vesicles of 0.1 ,um diameter (lip-AMB) (1.0 to 20.0 mg/kg of body weight) were compared with free amphotericin B (AMB) (0.5 to 2.0 mg/kg of body weight) in a murine model of disseminated candidiasis. CD2FI mice injected intravenously with 3 x 105 Candida albicans cells were treated with either single-or multiple-dose regimens. Untreated infected mice had a median survival of 7 days, with all mice dead by 12 days. Single doses of AMB resulted in a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
43
1
3

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(50 citation statements)
references
References 22 publications
3
43
1
3
Order By: Relevance
“…Liposomal amphotericin B (L-AMB; AmBisome) was found in preclinical studies to be as effective or more effective but less nephrotoxic than conventional amphotericin B in the treatment of experimental invasive pulmonary aspergillosis (13,15,37). Consistent with these findings are the results of four open label clinical trials which also demonstrated antifungal efficacy in immunocompromised patients (28,29,35) and a randomized trial in patients with invasive fungal infections complicating hematologic malignancies that found superior efficacy and safety (23).…”
supporting
confidence: 76%
“…Liposomal amphotericin B (L-AMB; AmBisome) was found in preclinical studies to be as effective or more effective but less nephrotoxic than conventional amphotericin B in the treatment of experimental invasive pulmonary aspergillosis (13,15,37). Consistent with these findings are the results of four open label clinical trials which also demonstrated antifungal efficacy in immunocompromised patients (28,29,35) and a randomized trial in patients with invasive fungal infections complicating hematologic malignancies that found superior efficacy and safety (23).…”
supporting
confidence: 76%
“…This preparation consisted of liposomes of less than 0.1 ,um in diameter. Gondal et al (3) reported that a similar preparation was effective in the therapy of experimental systemic candidiasis in mice. Sculier et al (21) Szoka et al.…”
Section: Resultsmentioning
confidence: 99%
“…Other investigators have used a variety of liposomal formulations of AmB to successfully treat experimental Candida (1,3,7,23), Histoplasma (21), and Cryptococcus (4) infections in mice. All of these studies demonstrated that incorporation of AmB into liposomes improved the therapeutic index.…”
mentioning
confidence: 99%
“…Serum samples were frozen at Ϫ80 C until measurement of the AMB concentrations by high-performance liquid chromatography (HPLC). AMB was extracted and quantified by modifying the procedure of Gondal et al (7). 1-Amino-4-nitronaphthalene (Sigma-Aldrich, Tokyo) was used as the internal standard.…”
mentioning
confidence: 99%